Expressão de genes da via de biossíntese do Hormônio Juvenil em Melipona scutellaris (Hymenoptera, Apidae, Meliponini) - Silva, Renato Pereira (2011)
In bees, juvenile hormone (JH) is a important factor in determining castes and also has a role in age polyethism. The first steps in the synthesis of JH are known as mevalonate pathway. In this pathway are present, among others, the 3-hydroxy-3- methylglutaryl-CoA reductase (HMGR) and farnesoic acid O-methyltransferase (FAMeT) enzymes. Thereafter, in insects occur successive reactions that culminate in JH-III production, in which the last reaction is catalyzed by the methylfarnesoate epoxidase (MFE). There is evidence that JH production is related both to the expression profile of these enzymes - in terms of mRNA production - and enzymatic activities. In this study, we analyzed the hmgr and mfe genes in different tissues, stages and castes of Melipona scutellaris. We also analyzed famet gene in larvae and adults of this species. Our results indicate that HMGR and MFE enzymes, in M. scutellaris, are probably involved in the synthesis of JH. Moreover, the MFE is a candidate for the rate limiting enzyme of this pathway. The FAMeT enzyme shows no evidence of relation to the synthesis of JH. Our results also suggest an inter-regulation between JH and ecdysteroids in M. scutellaris.